The species of genus Toninia of Gunib plato (Daghestan) - A. R. Gabibova; A. B. Ismailov; G. P. Urbanavichus (Юг России: экология, развитие, 2015)
The analysis of composition of genus, species of Toninia found on the territory of Gunib plato is given. In the result of treatment matherials determined 14 species and 4 subspecies of Toninia. 13 are new species for Daghestan and 3 new for Russia.